Can sleep proﬁles predict autistic traits in siblings of children with autism spectrum disorder? - Alshaimaa A. Naeem (Brazilian Association of Sleep and Latin American Federation of Sleep Societies, 2021)
Introduction: As the prevalence of ASD (autism spectrum disorder) continues to rise, so does the need to evaluate the impact of associated difficulties on both the diagnosed child and the immediate family. Objectives: The aim of the present study was to assess reports of sleep disturbance or abnormal sleep behaviours (sleep proﬁles) in the siblings of diagnosed autistic children (referred to throughout this study as high-risk siblings, or HR-sibs) and to determine if these sleep patterns correlated with evidence of disturbed sleep among their siblings who had full symptoms of autistic spectrum disorder. Material and Methods: This case control cross-sectional study investigated 64 autistic children, 80 HR-sibs, and 80 typically developing children. Each study subject was assessed for sleep problems and autistic traits through the use of a sleep-wake diary, a school sleep habit survey, and a childhood autism spectrum test. Results: Children with autism spectrum disorders and their HR-sibs showed no signiﬁcant differences regarding their sleep proﬁles. Typically, developing children had more middle insomnia than HR-sibs and had more wake latency. Conclusion: Increased risks for sleep problems in children with autism and their HR-sibs emphasized the importance of early screening for sleep problems in children with autism and their siblings.